Seasonal and spatial detection of pesticide residues in the ambient air of the Alsace region across different land use conditions - Dani Khoury; Supansa Chimjarn; Olivier Delhomme; Maurice Millet (Environment International)
Pesticide contamination in the atmosphere is an escalating environmental and public health concern, particularly in regions with intensive agricultural activity. This study investigates the distribution of 104 semi- and non-volatile pesticides in the air of the Strasbourg metropolitan area over a two-year period, located in the Alsace region of northeastern France. Using NMC@SiC passive samplers, we assessed pesticide concentrations across six diverse sampling sites—urban, suburban, and rural. A total of 104 pesticide compounds, including 35 fungicides, 43 herbicides, and 26 insecticides, were analyzed, with detection frequencies exceeding 30 % for multiple pesticides. Notably, banned pesticides such as chlorpyrifos (61 %, 0.2–1.2 ng m-3) and lindane (18 %, 0.1–0.9 ng m-3) were still present, indicating either illegal use or long-range atmospheric transport. Average total pesticide concentrations varied spatially, with herbicide levels ranging from 3.0 to 6.6 ng m-3, fungicides from 2.0 to 5.3 ng m-3, and insecticides showing higher variability between two periods: 3.4–12.6 ng m-3 (2018–2019) and 1.9–3.4 ng m-3 (2019–2020). Urban sites consistently exhibited higher pesticide burdens compared to suburban and rural sites. Statistically significant differences were observed between urban and rural zones for fungicides (p = 0.0176) and herbicides (p < 0.05), but not for insecticides. Temporal trends revealed clear seasonality, with higher pesticide concentrations during warmer months, supported by a positive correlation with temperature (r ∼0.5, p < 0.01) and a negative correlation with rainfall (r ∼–0.5 to –0.6, p < 0.01). Principal Component Analysis (PCA) distinguishing high total pesticide events and compositional shifts between fungicide- and insecticide-dominated periods. Back-trajectory confirmed predominant westerly and southwesterly airflows, indicating atmospheric transport from upwind agricultural areas. Risk assessments revealed extremely low chronic hazard quotients (HQ < 10-3) and lifetime cancer risks (< 10-6), indicating negligible health risks via inhalation exposure for both adults and children. These findings underscore the pervasive yet low-level nature of atmospheric pesticide contamination in peri-urban agricultural regions and highlight the need for continued monitoring to capture seasonal dynamics and potential regulatory impacts.